3D bioprinting of a tissue engineered human heart - Fakhruddin, Khalida; Abd Razak, Saiful Izwan; Mat Nayan, Nadirul Hasraf; Abdul Kadir, Mohammed Raﬁq (Springer Singapore, 2020)
Cardiovascular disease remains the leading cause of death in the world. Due to disadvantages of using the medical device to recover the function of the heart, researchers are getting interested to discover new intervention for cardiovascular diseases. Bioprinting is one facet of tissue engineering which has been emerging in recent years to build a three dimensional constructs containing biological cells and show a promising potential to overcome the challenges of current intervention of cardiovascular diseases. In this chapter, authors attempt to review and discuss on bioprinting of tissue engineered human heart. Explanation will be based on introduc-tion of bioprinting, the materials it used, the potential of cell sources and previous work done.